2015
DOI: 10.1016/j.jpcs.2014.12.016
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure phases of SF6 up to 32GPa from X-ray diffraction and Raman spectroscopy

Abstract: X-ray diffraction and Raman spectroscopy were employed to study the phase diagram of SF 6 at pressures up to 32 GPa. The known phase transformation of SF 6 phase I to phase II at around 2 GPa was confirmed. Discontinuities in the pressure dependence of the Raman frequencies and positions of X-ray reflections indicate further phase transitions at 10(1) and 19(1) GPa.The crystal structures of phases I and II were determined using single crystal X-ray diffraction. The structure of phase I corresponds to the "plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…The SF 6 phase diagram as a function of pressure has been explored by X-ray diffraction up to 32 GPa. 23 A phase transition to the same crystal structure of the low temperature phase described by Cockcroft and Fitch 31 has been observed at 2 GPa (phase II). Further transitions have been observed to occur at 12 GPa (phase III) and 24 GPa (phase IV) as evidenced by the appearance of new lines in the diffraction pattern and changes in the Raman spectrum.…”
Section: Phase Diagram Of Sulfur Hexafluoridesupporting
confidence: 54%
See 3 more Smart Citations
“…The SF 6 phase diagram as a function of pressure has been explored by X-ray diffraction up to 32 GPa. 23 A phase transition to the same crystal structure of the low temperature phase described by Cockcroft and Fitch 31 has been observed at 2 GPa (phase II). Further transitions have been observed to occur at 12 GPa (phase III) and 24 GPa (phase IV) as evidenced by the appearance of new lines in the diffraction pattern and changes in the Raman spectrum.…”
Section: Phase Diagram Of Sulfur Hexafluoridesupporting
confidence: 54%
“…It can be noted that the scaled calculated frequencies agree quite satisfactorily with the crystal frequencies. 22 , 23 This may imply that the XP-PCM approach somehow accounts for the static field acting on the molecule albeit not (obviously) for the intermolecular coupling giving rise to the Davydov splitting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high-pressure behaviour of SF 6 has been studied by Sasaki et al [10] up to 10 GPa by Raman spectroscopy who found two different crystalline phases, denoted as phase I and phase II. We recently explored the phase diagram of SF 6 by means of X-ray diffraction and micro-Raman spectroscopy up to 32 GPa and observed two additional phase transformations at 10 GPa and 19 GPa, respectively [11]. The SF 6 molecule was stable up to the highest applied pressure at ambient temperature.…”
Section: Introductionmentioning
confidence: 99%